A review of recent progress in biogas upgrading: With emphasis on carbon capture. (May 2022) - Aghel, Babak; Behaein, Sara; Wongwises, Somchai; Shadloo, Mostafa Safdari
Abstracts: Carbon dioxide (CO2 ) and methane (CH4 ) constitute biogas that is formed from landfill and anaerobic digestion processes. Furthermore, raw biogas consists of minor quantities of hydrogen sulfide (H2 S), hydrogen (H2 ), ammonia (NH3 ), carbon monoxide (CO), nitrogen (N2 ), and oxygen (O2 ). As a renewable energy, biogas can be obtained and upgraded to produce biomethane for injection into the natural gas grid or applied as fuel in-vehicle, for on-site heat, and for steam/electricity generation in the industry. Different technologies are thus applied for the removal of such components, converting biogas to biomethane. Bottom ash (BA) upgrading and alkaline with regeneration (AwR) are two other novel technologies that mineralize carbon not only to remove CO2 but also store it from biogas using waste from municipal solid waste incinerators containing calcium. This research reviews the most widespread technologies and recent studies on the removal of CO2, as well as studies several parameters, merits, and demerits of these methods. Graphical abstract: Image 1 Highlights: Recent advances in biogas upgradation methods in different views are compared. The BA upgrading and AwR are regarded as environmentally-friendly techniques. Technology selection can be considered by the specific conditions and strategies. Captured carbon from biogas can be used to produce chemical materials.